EROSION-RESISTANT COMPOSITE MATERIAL - Dangi, Ugersan (Innovative Research Thoughts, 2018)
An erosion-resistant composite material is a material that is designed to resist the effects of erosion caused by various factors, such as high-velocity fluids, abrasive particles, and weathering. A polymer matrix that has been reinforced with one or more other components, such as ceramics, metals, or fibers, makes up an erosion-resistant composite material in most cases. The particular mix of the matrix and reinforcement components determines the characteristics of the erosion-resistant composite material. For instance, including ceramics like SiC into the polymer matrix can increase the composite's hardness, wear resistance, and thermal stability, enabling it to be used in demanding conditions. Several processing techniques have been developed for the fabrication of erosion-resistant composite materials, including injection molding, extrusion, and compression molding. The choice of processing technique depends on the desired properties and the specific application of the composite. Erosion-resistant composite materials can find numerous applications in various industries, including aerospace, automotive, and defense. The erosion resistance of these composites makes them suitable for use in various components, such as fan blades, impellers, and nozzles.